2020
DOI: 10.1262/jrd.2020-026
|View full text |Cite
|
Sign up to set email alerts
|

Conditional kisspeptin neuron-specific <i>Kiss1</i> knockout with newly generated <i>Kiss1</i>-floxed and <i>Kiss1</i>-Cre mice replicates a hypogonadal phenotype of global <i>Kiss1</i> knockout mice

Abstract: The present study aimed to evaluate whether novel conditional kisspeptin neuron-specific Kiss1 knockout (KO) mice utilizing the Cre-loxP system could recapitulate the infertility of global Kiss1 KO models, thereby providing further evidence for the fundamental role of hypothalamic kisspeptin neurons in regulating mammalian reproduction. We generated Kiss1-floxed mice and hypothalamic kisspeptin neuron-specific Cre-expressing transgenic mice and then crossed these two lines. The conditional Kiss1 KO mice showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Thus, it is speculated that the AVPV Kiss1 mRNA expression would be somehow upregulated by non-kisspeptin signal(s) from the ARC KNDy neurons and/or the interneuron(s) under the control of the ARC KNDy neurons. This notion is consistent with our recent study, showing that AVPV Kiss1 expression was also deprived in conditional ARC Kiss1 KO female mice (45). Indeed, a previous anterograde tracing study indicated the projection of ARC KNDy neurons toward AVPV kisspeptin neurons (46).…”
Section: Physiologysupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, it is speculated that the AVPV Kiss1 mRNA expression would be somehow upregulated by non-kisspeptin signal(s) from the ARC KNDy neurons and/or the interneuron(s) under the control of the ARC KNDy neurons. This notion is consistent with our recent study, showing that AVPV Kiss1 expression was also deprived in conditional ARC Kiss1 KO female mice (45). Indeed, a previous anterograde tracing study indicated the projection of ARC KNDy neurons toward AVPV kisspeptin neurons (46).…”
Section: Physiologysupporting
confidence: 93%
“…ISH for Kiss1 and Cre Expression in the AAV-Cre-Induced ARC Kiss1 KO Rats. The ISH was performed as described previously (33,45,59,60). Briefly, the sections were hybridized overnight at 60°C with DIG-labeled anti-sense cRNA probe for either Kiss1 (position 33-349, AY196983) or Cre (position 485-1516, X03453).…”
Section: Methodsmentioning
confidence: 99%
“…Kiss1 -floxed mice were bred in-house from homozygous breeding pairs of Kiss1 -floxed mice, in which exon 3 of the Kiss1 gene were floxed with LoxP sites, as described in detail elsewhere [ 24 ]. Animals were housed in a controlled environment (14L:10D, lights on at 0500 h, at 22 ± 2˚C) with free access to food and water.…”
Section: Methodsmentioning
confidence: 99%
“…Kiss1-floxed mice were bred in-house from homozygous breeding pairs of Kiss1-floxed mice, in which exon 3 of the Kiss1 gene were floxed with LoxP sites, as described in detail elsewhere [24].…”
Section: Animalsmentioning
confidence: 99%
“…The mechanism generating pulsatile GnRH secretion is called the GnRH pulse generator, and its activity is suggested to be modulated by steroid feedback actions and various environmental factors, such as nutritional status, stress, and suckling stimulus. Kisspeptin (first named metastin) was identified as an endogenous ligand for GPR54 [3], and accumulating evidence suggests that kisspeptin-GPR54 signaling controls reproductive function via the stimulation of GnRH/gonadotropin release in several mammalian species, such as rodents [4][5][6][7], ruminants [8][9][10][11][12], and primates [13][14][15]. Loss of function studies of kisspeptin or GPR54 by genetic mutation or conventional knockout showed hypogonadotropic hypogonadism with low to undetectable luteinizing hormone (LH) levels, which clearly demonstrates that kisspeptin-GPR54 signaling is a fundamental factor for stimulating GnRH/LH secretion in rodents and humans [16][17][18].…”
mentioning
confidence: 99%